Factors that drive peer dissemination of agricultural information: evidence from northern Ghana. Issue 5 (4th July 2021) - Etwire, Prince Maxwell; Martey, Edward; Goldsmith, Peter
ABSTRACT : This study relies on a triple-hurdle model to estimate the factors that determine farmers' decision to participate in a peer dissemination project and then share the knowledge gained with other farmers. The first hurdle estimates show that proximity, income and social contacts determine participation. The second hurdle estimates further show that access to information, being a male and farming experience have positive effects on facilitating a higher level of participation. Estimates of the final hurdle suggest that geographical location plays a role in determining the number of farmers that participants of a peer dissemination project can contact.